Resting state functional MRI reveals abnormal network connectivity in neurofibromatosis 1. Issue 11 (25th August 2015) - Tomson, Steffie N.; Schreiner, Matthew J.; Narayan, Manjari; Rosser, Tena; Enrique, Nicole; Silva, Alcino J.; Allen, Genevera I.; Bookheimer, Susan Y.; Bearden, Carrie E.
Abstract Neurofibromatosis type I (NF1) is a genetic disorder caused by mutations in the neurofibromin 1 gene at locus 17q11.2. Individuals with NF1 have an increased incidence of learning disabilities, attention deficits, and autism spectrum disorders. As a single‐gene disorder, NF1 represents a valuable model for understanding gene–brain–behavior relationships. While mouse models have elucidated molecular and cellular mechanisms underlying learning deficits associated with this mutation, little is known about functional brain architecture in human subjects with NF1. To address this question, we used resting state functional connectivity magnetic resonance imaging (rs‐fcMRI) to elucidate the intrinsic network structure of 30 NF1 participants compared with 30 healthy demographically matched controls during an eyes‐open rs‐fcMRI scan. Novel statistical methods were employed to quantify differences in local connectivity (edge strength) and modularity structure, in combination with traditional global graph theory applications. Our findings suggest that individuals with NF1 have reduced anterior–posterior connectivity, weaker bilateral edges, and altered modularity clustering relative to healthy controls. Further, edge strength and modular clustering indices were correlated with IQ and internalizing symptoms. These findings suggest that Ras signaling disruption may lead to abnormal functional brain connectivity; further investigation into the functional consequences of these alterations in both humans and in animal models is warranted. Hum Brain Mapp 36:4566–4581, 2015. © 2015 Wiley Periodicals, Inc.